Prenatal contraceptive counseling and method provision after childbirth - Nelson AL (Dove Medical Press, 2015)
Anita L Nelson Los Angeles Biomedical Research Institute, Harbor-UCLA Medical Center, Torrance, CA, USA Abstract: Postpartum contraception is undergoing major changes, not only in timing, but also in content. Failure to provide immediate postpartum contraception contributes to the problems of unintended pregnancies and rapid repeat pregnancy because often the highest-risk women do not return for postpartum care. If they do attend that visit, they have often lost the insurance coverage that would enable them to use the most effective forms of birth control. Most of the issues surrounding early initiation of progestin-only methods and breastfeeding have been favorably resolved. In some cases, insurance coverage for delivery has been expanded to cover the costs of providing intrauterine devices and implants before the woman is discharged home. All of these new opportunities shift the burden of counseling about postpartum contraception onto the shoulders of the prenatal care provider. This article provides information about the advantages and disadvantages of providing immediate postpartum contraception with each of the eligible methods so clinicians can provide the needed counseling both during pregnancy and during hospitalization for delivery. It also provides guidance for initiation of bridging contraception, if needed, to initiate a method for a woman later in the postpartum period. Keywords: postpartum contraception, counseling, breastfeeding, implants, IUDs, hormonal methods